ULKUS KORNEA PERFORASI SEBAGAI DAMPAK PENGGUNAAN STEROID TANPA INDIKASI: SEBUAH LAPORAN KASUS - Vilado, Irene; Herwindo, Dicky; David, Nathanael; Chandra, Beryl; Sagita, Zendy (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Corneal ulcer is an infectious condition of the cornea that involves the epithelial layer to the stroma. Steroid use to treat corneal ulcer without indication is still a massive issue especially in primary-level healthcare facility (PLHF) and may potentially cause various complications. Steroids can delay epithelial healing and induce perforation, and also neutrophil inhibition that will lead to infection exacerbation. A holistic understanding of corneal ulcers, especially the approach to diagnosis, both clinically and diagnostics work up, and effective management for patients are very important to understand, especially in PLHF. This case report aims to provide knowledge regarding the steroid management of corneal ulcers and periosteal graft use in perforated corneal ulcers. . Male, 39 year old, comes to RSUD Dr. Saiful Anwar Malang (RSSA) with chief complaints of redness, pain, and white lesion that progressively widened in left eye. Patient had a history of trauma caused by inflorescence one month ago. White lesion was first only a pinpoint lesion but progressively widened. Patient have sought medical advice to PLHF and secondary-level healthcare facility (SLHF), then referred to RSSA with potential complication occurring. Approach to diagnosis holistically and management with correct indication is important to prevent corneal ulcer perforation especially due to steroid use.